ANALYSIS OF METHODS OF APPLICATION OF POLYMER COATING ON LIGHT INDUSTRY PARTS ON ROLLING MACHINES - MAZUR, ANDRIY; HORIASHCHENKO, SERHIY (Herald of Khmelnytskyi National University. Technical sciences, 2025)
This article explores the prospects of using roller coating machines for the application of protective polymer films on leather components in the production of fashion and technical leather goods. Roller coating is recognized as an efficient and sustainable technology due to its high precision in layer thickness control, reduced material consumption, and process repeatability. The paper presents an overview of the operating principles of different types of roller mechanisms, including single-roller, double-roller, and multi-roller systems with controlled pressure and gap settings. Special attention is paid to the technical and functional advantages of modern roller coating equipment, such as the Synchrocoat and Multicoat models by Bergi S.p.A., which offer consistent coating quality and compatibility with a wide range of polymers, including polyurethane, acrylic, and wax-based compounds.The study highlights the technological features of roller coating, such as adjustable speed, pressure, and coating viscosity, allowing fine-tuned application onto various types of leather with different surface properties. Furthermore, the integration of automatic control systems and sensor-based feedback loops ensures uniform film thickness and strong adhesion without damaging the flexible leather substrates. Comparative analysis of international equipment specifications is provided, revealing trends in automation, energy efficiency, and multi-layer application capabilities.The article also includes a review of recent academic and industrial research focused on the mechanical, adhesive, and aesthetic properties of coated leather products. These studies underline the importance of optimal coating parameters and the influence of machine configuration on the final product performance. The conclusion emphasizes that roller coating technology offers significant potential for improving product durability and appearance while supporting sustainable production practices. The results of this work may inform the development of advanced coating lines for the leather industry and encourage further innovation in environmentally conscious surface treatment methods.
Keywords: polymer; rolls; equipment; light industry parts; methods